Analisis Implementasi Kerjasama Sister-Province Antara Provinsi Yogyakarta Dengan Gyeongsangbuk-Do Dalam Pengembangan Desa - Dewi, Sannya Pestari (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
Sister-city cooperation between Yogyakarta and Gyeongsangbuk-Do has existed for 10 years. It has shown that regional authorities are able to carry out cooperation across national borders continously, especially in developing rural areas. Sumbermulyo has unique characteristics, which has a diversity of religious adherents who become religious tourism. This village is also one of the largest rice producers in D.I Yogyakarta. However, the low level of education in this region also complements the complexity of the implementation of the collaboration between the two parties. This study aims to analyze implementation of sister-city cooperation between Yogyakarta and Gyeongsangbuk-Do in the development of Sumbermulyo village, Bantul. The implementation of sister-city cooperation is examined by model of implantation policy with four indicators namely communication, resources, disposition, and bureaucratic structure. From the four indicators it was found that the cooperation of D.I Yogyakarta and Gyeongsangbuk-Do in the development of Sumbermulyo village was not successful in its implementation, with only the disposition indicator being met from the program. This is also illustrated by the implementation of program only in the second year of the agreed five years. The failure of this program made the evaluation for the government in the application of sister-province further collaboration.